2022
DOI: 10.1101/2022.11.18.517046
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rising SARS-CoV-2 Seroprevalence and Patterns of Cross-Variant Antibody Neutralization in UK Domestic Cats

Abstract: Recent evidence confirming cat-to-human SARS-CoV-2 transmission has highlighted the importance of monitoring infection in domestic cats. Although the effects of SARS-CoV-2 infection on feline health are poorly characterized, cats have close contact with humans, and with both domesticated and wild animals. Accordingly, they could act as a reservoir of infection, an intermediate host and a source of novel variants. To investigate the spread of the virus in the cat population, serum samples were tested for SARS-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…For samples with one or more titers, the pseudotype variant that generated the highest titer indicated the variant the animal had likely been infected with. The assay was performed as previously described by Davis et al [ 57 , 58 ]. For this study, the SARS-CoV-2 spike glycoprotein expression constructs were synthesized using GenScript (Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…For samples with one or more titers, the pseudotype variant that generated the highest titer indicated the variant the animal had likely been infected with. The assay was performed as previously described by Davis et al [ 57 , 58 ]. For this study, the SARS-CoV-2 spike glycoprotein expression constructs were synthesized using GenScript (Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…As with all studies of SARS-CoV-2 it is important to assess the individual virus lineages (22), especially with the Omicron variant, as substantial virological changes have occurred as the pandemic has proceeded. Based on the timing of the study, we sampled infections caused predominantly by pre-VOC SARS-CoV-2 (from the B.1 lineage, spanning both S:G614G and S:614D).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have, however, demonstrated cats' high susceptibility to SARS-CoV-2 infections and their potential to transmit the virus through close contact (11). Numerous studies have now reported seroprevalence of SARS-CoV-2 in domestic, shelter, and stray cats, yielding variable prevalence (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Despite now extensive global documentation, data on the seroprevalence of SARS-CoV-2 in U.S. domestic cats remains relatively scarce (23)(24)(25)(26)(27), especially during the early stages of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, moderate levels of SARS-CoV-2 seroprevalence in domestic cats have been documented in multiple publications [12][13][14], based on the analysis of remnant diagnostic samples submitted for other purposes. Despite this appreciable seroprevalence, veterinary diagnostic testing of domestic animals for SARS-CoV-2 is rarely performed due to the very narrow testing criteria dictated by government guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Cats are known to generate a robust neutralising antibody response to SARS-CoV-2, which enables animals to resist re-infection [27], as well as an IgG response against the Spike and Nucleocapsid proteins of multiple different variants [14,21,28].…”
Section: Introductionmentioning
confidence: 99%